Exploring a capacity to screen of the European Portuguese version of the 15-item Geriatric Depression Scale - João Luís Alves Apóstolo; Bobrowicz-Campos, E.; Ivo Alexandre Carvalho dos Reis; Susana Justo Henriques; Carla Alexandra Veiga Correia (Revista de Psicopatología y Psicología Clínica, 2018)
Abstract: The aim of this study was to analyze the screening performance of the European Portuguese version of the 15-item Geriatric Depression Scale (GDS-15) against DSM-5 diagnostic criteria for major depressive episode. The study was multicentre and involved 139 older adults recruited in the context of primary healthcare. Twenty-three participants were diagnosed with clinical depression. Sensitivity and specificity for different cut-off points were determined based on ROC curve analyses. The cut-off point ≥ 4.5 provided optimal sensitivity (95.7%) and specificity (52.6%) rates. After exclusion from the analysis of illiterate participants’ data, the optimal cut-off point remained unchanged. The European Portuguese version of GDS-15 is an effective tool for depression screening in older adults. Further studies are needed to verify if there are factors, other than formal education, that may influence the scale’s performance.